Presenting medical statistics from proposal to publication - Peacock, Janet (Janet L.); Kerry, Sally M.; Balise, Raymond R. ([Oxford] : Oxford University Press, 2017)
Designed for researchers presenting medical statistics for publication, this guide emphasises the principles of good presentation through examples. It contains tips, information boxes and figures, as well as references for the statistical methods used. It also presents the different stages of the research process.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 1, 2017).
Keywords: Medical statistics